1975
DOI: 10.1182/blood.v46.1.65.65
|View full text |Cite
|
Sign up to set email alerts
|

The relative spatial distributions of CFUs and CFUc in the normal mouse femur

Abstract: Femoral bone marrow was divided longitudinally into two groups of cells of varying size. By assaying CFU and CFU in the two zones of the marrow, their distributions across the diameter of the femur was determined. It is shown that the concentration of CFU increases from the femoral axis (15 CFU/105 bone marrow cells) to the bone surface (44 CFU/105 cells), obeying approximately a square-law relationship. The CFU concentration, on the other hand, increases from the femoral axis (32CFU/105 cells) to a peak value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
1
1

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(101 citation statements)
references
References 7 publications
2
92
1
1
Order By: Relevance
“…28 The above-mentioned label-retaining assays both confirm and extend previous classical studies in which morphological criteria and colony-forming assays were used to show that HSCs are enriched in the endosteal region compared with the central part of the BM, which is rather populated by progenitors and more differentiated cell types. 35,36 In addition, it was shown that BrdU + LRCs expressing c-Kit could be in direct contact with osteoblasts at the endosteum, and that both of these cell types express the cell adhesion anchor N-cadherin. 28 This led to the hypothesis that HSCs are anchored to niche osteoblasts via homotypic N-cadherin interactions.…”
Section: Hsc Identification By Label-retaining Assaysmentioning
confidence: 99%
“…28 The above-mentioned label-retaining assays both confirm and extend previous classical studies in which morphological criteria and colony-forming assays were used to show that HSCs are enriched in the endosteal region compared with the central part of the BM, which is rather populated by progenitors and more differentiated cell types. 35,36 In addition, it was shown that BrdU + LRCs expressing c-Kit could be in direct contact with osteoblasts at the endosteum, and that both of these cell types express the cell adhesion anchor N-cadherin. 28 This led to the hypothesis that HSCs are anchored to niche osteoblasts via homotypic N-cadherin interactions.…”
Section: Hsc Identification By Label-retaining Assaysmentioning
confidence: 99%
“…Long-term HSC originate short-term HSC, which then undergoes several commitments and massive proliferation, until reaching full differentiation. Each step in this cascade demands a different combination of cytokines, chemokines, extracellular matrix interactions and cellcell interactions, which are offered by different stromal cell types [Lord et al, 1975;Lambertsen and Weiss, 1984;Taichman and Emerson, 1994;Calvi et al, 2003;Zhang et al, 2003;Arai et al, 2004;Stier et al, 2005;Sugiyama et al, 2006;Taichman et al, 1996Taichman et al, , 2010Balduino et al, 2005Balduino et al, , 2012Ding et al, 2012]. The notion that different niches compose the bone marrow microenvironment was envisioned by Lord and colleagues [Lord et al, 1975].…”
Section: Not Too Far From the Surfacementioning
confidence: 99%
“…Histological and functional assays indicated that HSC and multipotent progenitors preferentially colonize the endosteal and subendosteal regions, in close association with the bone surface. Conversely, committed progenitors and differentiated cells are distributed in the central and perisinusoidal regions, respectively [Lord et al, 1975;Lambertsen and Weiss, 1984;Taichman and Emerson, 1994;Nilsson et al, 2001;Arai et al, 2004;Kiel et al, 2005;Jung et al, 2006;Lo Celso et al, 2009].…”
Section: Not Too Far From the Surfacementioning
confidence: 99%
“…2 Searching the location of stem cells in the BM, initial studies have found a higher concentration of colony-forming units in spleen (CFU-S) near the bone surface than in the central longitudinal axis of the femoral cavity. 3 Further studies then revealed that fluorescently labeled Lin neg cells tend to localize predominantly in the endosteum 15 h after transplantation. 4 Confocal microscopy imaging with lineage staining and BrdU retention studies has revealed that stem cells associate closely with spindle-shaped N-cadherin-expressing osteoblasts that line the endosteal bone, 5 and that the stem cell pool size expands in mice genetically engineered to exhibit enhanced osteoblastic activity.…”
Section: Introductionmentioning
confidence: 99%